ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DALAM MENINGKATKAN PROFIL PELAJAR PANCASILA DI KELAS V SDN 3 BANJAR AGUNG - denisaaa Dara; Lailatus Shofi’iyah; Alfina Amri Aulia; Riana Meilani Putri (STKIP Subang, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum and the achievement of the Pancasila Student Profile (P5) in Grade V at SDN 3 Banjar Agung. The Merdeka Curriculum is an educational policy that provides flexibility for teachers and students in the learning process, with an emphasis on character building, 21st-century skills development, and project-based learning. One of its core components is the Pancasila Student Profile Reinforcement Project (P5), which aims to shape student character based on six key dimensions: faith and noble character, global diversity, mutual cooperation, independence, critical thinking, and creativity. The research used observation and interviews with Grade V teachers. The results show that the Merdeka Curriculum has been implemented since the 2023/2024 academic year through various active and collaborative activities, such as making traditional herbal drinks (jamu), planting medicinal plants (toga), and performing social-themed dramas. These activities have successfully fostered student character in aspects of tolerance, teamwork, creativity, and awareness of local cultural values. However, the implementation of P5 also faces challenges, such as limited facilities, a lack of teacher training, and low student readiness for independent learning. These findings highlight that the success of the Merdeka Curriculum implementation highly depends on the support of all stakeholders, including teachers, parents, and the school environment. Strong collaboration is essential to enhance the effectiveness of learning and the overall achievement of the Pancasila Student Profile.